2018
DOI: 10.21037/cdt.2017.09.13
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal aortic aneurysm screening: concepts and controversies

Abstract: Abdominal aortic aneurysms (AAAs) are a leading cause mortality and morbidity but often go undiagnosed until late stages unless imaging is performed. In 2005, the United States Preventive Services Task Force (USPSTF) for the first time recommended one-time ultrasound screening for elderly male smokers and selective screening in other populations. These guidelines were reaffirmed and updated in 2014; a proposal for potential further revisions is now in early planning stages. In this article, we review the past … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 39 publications
0
12
0
1
Order By: Relevance
“…Finally, 747 valid measurements were adopted (97.6%). After a 5-year follow-up, 71 SAA patients were withdrawn (8.5%), of whom 48 were lost to contact, 12 were died of disease (5 from cerebral hemorrhage, 1 from pancreatic cancer, 1 from lung cancer, 1 from prostate cancer, 1 from respiratory failure, 1 from gastric cancer, 1 from colon cancer, and 1 from accidental death), 11 greater than 2.7 cm (OR = 2.828), smoking after 30 years old (OR = 2.783), moderate hypertension (OR = 2.63), severe hypertension (OR = 2.917), and blood pressure variability (OR = 3.164) had significant statistical significance (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, 747 valid measurements were adopted (97.6%). After a 5-year follow-up, 71 SAA patients were withdrawn (8.5%), of whom 48 were lost to contact, 12 were died of disease (5 from cerebral hemorrhage, 1 from pancreatic cancer, 1 from lung cancer, 1 from prostate cancer, 1 from respiratory failure, 1 from gastric cancer, 1 from colon cancer, and 1 from accidental death), 11 greater than 2.7 cm (OR = 2.828), smoking after 30 years old (OR = 2.783), moderate hypertension (OR = 2.63), severe hypertension (OR = 2.917), and blood pressure variability (OR = 3.164) had significant statistical significance (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, almost one-third (30.1%) of patients have undergone a diagnostic imaging test within 5 years of screening evaluation that can serve to confirm or refute the presence of aortic ectasia or AAA. National guidelines and a patient’s imaging history therefore represent opportunities for radiology departments to avoid unnecessary imaging and save health-care costs, 12 making AAA screening more cost effective than what has already been shown. 13 We found that, by adhering to CSVS guidelines and reviewing prior imaging tests performed within 5 years, our province could avoid over half (51.2%) of all screening US examinations and save an estimated CAD$52 362.45 per year.…”
Section: Discussionmentioning
confidence: 99%
“…The development of an aneurysm in the abdominal aorta seems to be the interaction of environmental and genetic factors [1, 2]. The pathophysiology of this disease process consists in the degradation of the extracellular matrix of the blood vessel wall in response to the accumulation of inflammatory cells such as macrophages and lymphocytes, and the activation of matrix metalloproteinases; and the resulting inflammation, tissue destruction and necrosis produce more cycles of inflammation [2].…”
Section: Discussionmentioning
confidence: 99%
“…Abdominal Aortic Aneurysms (AAA) are defined as focal dilations located in the abdominal aorta from a diameter of at least 50% greater than the normal and healthy segment of this blood vessel (Fig. 1) [1, 2]. The most common location of this disease process is the infrarenal aorta where a diameter that is equal or greater than 30 mm measured by Computed Tomography Angiography (CTA) establishes the diagnosis of AAA [1, 2], Aortic aneurysms of atherosclerotic or degenerative etiology are relatively frequent among men over 65-year-old with a reported prevalence ranging from 3 to 7% determined by imaging studies [13]; and its most feared complication is the aneurysm rupture with an associated mortality above 80%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation